Epidemiology and etiology of fractures in children and adolescents - Aborukbah, Abdullah Fuad; Abu Alsaud, Sajidah Hisham; Aldhafyan, Abdulmalik Essa; Hamdan, Abdulilah Fareed; Alaboudi, Abdullah Rashid; Sharahili, Rami Moraya; Alsharif, Abdullah Abdulaziz; Albahraini, Farah KH; Alsahli, Majed Abdulrahman; Alazemi, Abdulaziz M.; Alghamdy, Basel Salem (International Journal Of Community Medicine And Public Health, 2023)
Fractures in children and adolescents are a significant public health concern. The incidence of fractures varies based on age, sex, and anatomical site, with falls, sports-related injuries, motor vehicle accidents, child abuse, and pathological conditions identified as primary causes. Risk factors such as age, sex, physical activity, bone mineral density, body composition, and genetic factors contribute to fracture occurrence. Preventive measures targeting modifiable risk factors and promoting safety in physical activities are crucial for reducing the burden of fractures in children and adolescents. This review aims to provide a comprehensive understanding of the epidemiology and etiology of fractures in children and adolescents. Understanding the epidemiological patterns and etiological factors can guide the development of effective prevention strategies and optimize fracture management in this population.